2020
DOI: 10.1186/s40249-020-00697-0
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiologically characteristics of human brucellosis and antimicrobial susceptibility pattern of Brucella melitensis in Hinggan League of the Inner Mongolia Autonomous Region, China

Abstract: Background: Hinggan League is located in the Northeast of the Inner Mongolia Autonomous Region, the historically endemic area of animal and human brucellosis. In this study, the epidemiological characteristics of human brucellosis were analyzed, and the genotypic profile and antimicrobial susceptibilities of Brucella melitensis strains isolated from humans in Hinggan League were investigated. Methods: The epidemic characteristics were described using case number, constituent ratio, and rate. The 418 human bloo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 38 publications
3
21
0
Order By: Relevance
“…Seasonality features included an incidence peak in March to August. Moreover, the 50–59-year-old age group had more cases; the ratio of males to females of 3.40:1 was similar to the results of previous studies 16 , 23 . Another study showed that a total of 1149 human brucellosis data points were collected during 2014–2018 in Huludao (China), with a mean age of 49.59 ± 13.14 years, and 75.7% were male 24 .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Seasonality features included an incidence peak in March to August. Moreover, the 50–59-year-old age group had more cases; the ratio of males to females of 3.40:1 was similar to the results of previous studies 16 , 23 . Another study showed that a total of 1149 human brucellosis data points were collected during 2014–2018 in Huludao (China), with a mean age of 49.59 ± 13.14 years, and 75.7% were male 24 .…”
Section: Discussionsupporting
confidence: 90%
“…Isolation and culture of clinical strains were performed according to standard procedures in a biological safety II (p2) laboratory 16 . Briefly, five (~ 10 mL) blood samples were collected from each suspected patient and injected into a biphasic culture bottle (Germany, bioMérieux; China, Barrett Biotechnology (Zhengzhou) Co., Ltd.) in biosafety combination and incubated at 37 °C with 5% CO 2 for 2–4 weeks.…”
Section: Methodsmentioning
confidence: 99%
“…This may be due to the fact that most of the population entering the province from abroad is the working population who aged 20-60, so the incidence of malaria in this age group is signi cantly affected by COVID-19. The results also showed that the incidence of brucellosis in the age group > 20 years was lower than during the same period of previous four years, while the incidence of brucellosis in the age group < 20 years was still within the range of that documented during the same period of previous four years,This may be due to the higher prevalence of brucellosis among farmers [27], and the age of farmers are mainly > 20 years, so the people in this age group were more likely to be affected by COVID-19. Moreover, we found that the incidence of HF in the age group of 20-50 years was lower than that of the same period during the previous four years, this is because the incidence of HF is mainly in the age group of 20-60 years, young and middle-aged farmers have more eld work and have greater exposure to rats and their pollutants.…”
Section: Discussionmentioning
confidence: 58%
“…Our results were similar to many other pieces of literature reported from other provinces or cities in China. 5 , 22 , 23 …”
Section: Discussionmentioning
confidence: 99%
“…Our results were similar to many other pieces of literature reported from other provinces or cities in China. 5,22,23 The conclusion drawn from previous studies, the positive rates of brucellosis from blood cultures had a wideranged from 16% to 90%. 24 This was consistent with the current study of 46.8% positive rate and mostly were discovered in the acute phase of brucellosis.…”
mentioning
confidence: 95%